Panorama of wind energy in the state of Rio Grande do Norte in 2004-2017 - Dantas, Gerbeson Carlos Batista; Rodrigues, Marcus Vinícius Sousa; Silva, Leonardo Magalhães Xavier; Aquino, Marisete Dantas De; Thomaz, Antônio Clécio Fontelles (Estudos Avançados, 2021)
The objective of this paper is to provide an overview of wind energy in the state of Rio Grande do Norte between 2004 and 2017, demonstrating the state’s strength in electric power generation from wind. This objective is achieved through an extensive bibliographic survey of academic sources and websites of official wind energy organizations. Exponential growth of wind energy generation had been observed at this state. Between 2004 and 2017, installed capacity grew from 1.8 MW to 3,3625.50 MW. Rio Grande do Norte accounts for 32.72% of all wind energy generation in Brazil and for 38.95% in the Northeastern region, totaling 13.24TWh with 133 wind farms established at the state. Rio Grande do Norte has an average generation capacity factor of 44.4%, the 5th position in the Brazilian ranking, behind the states of Maranhão (68%), Bahia (48.5%), Pernambuco (48.3%), and Piauí (46.1%). Despite this, the state’s generation capacity factor is higher than the national average (42.9%) and the global average (24.7%). Although Rio Grande do Norte has experienced vertiginous growth in wind energy generation, there is much room for further growth. Federal and local governments must develop incentive policies for wind energy to ensure that Rio Grande do Norte will achieve its maximum potential of clean electricity generation at competitive costs compared to other energy sources.